Smokers Who Try E-Cigarettes to Quit Smoking: Findings From a Multiethnic Study in Hawaii - Pokhrel, Pallav (American Public Health Association, 2013)
Objectives. We characterized smokers who are likely to use electronic or “e-”cigarettes to quit smoking. Methods. We obtained cross-sectional data in 2010–2012 from 1567 adult daily smokers in Hawaii using a paper-and-pencil survey. Analyses were conducted using logistic regression. Results. Of the participants, 13% reported having ever used e-cigarettes to quit smoking. Smokers who had used them reported higher motivation to quit, higher quitting self-efficacy, and longer recent quit duration than did other smokers. Age (odds ratio [OR] = 0.98; 95% confidence interval [CI] = 0.97, 0.99) and Native Hawaiian ethnicity (OR = 0.68; 95% CI = 0.45, 0.99) were inversely associated with increased likelihood of ever using e-cigarettes for cessation. Other significant correlates were higher motivation to quit (OR = 1.14; 95% CI = 1.08, 1.21), quitting self-efficacy (OR = 1.18; 95% CI = 1.06, 1.36), and ever using US Food and Drug Administration (FDA)–approved cessation aids such as nicotine gum (OR = 3.72; 95% CI = 2.67, 5.19). Conclusions. Smokers who try e-cigarettes to quit smoking appear to be serious about wanting to quit. Despite lack of evidence regarding efficacy, smokers treat e-cigarettes as valid alternatives to FDA-approved cessation aids. Research is needed to test the safety and efficacy of e-cigarettes as cessation aids.